Grey matter abnormalities in first‐episode mania: A systematic review and meta‐analysis of voxel‐based morphometry studies. (8th October 2020) - Keramatian, Kamyar; Chakrabarty, Trisha; Saraf, Gayatri; Pinto, Jairo V.; Yatham, Lakshmi N.
Abstract: Objectives: It has been proposed that different stages of bipolar disorder may be underpinned by distinct neurobiological substrates. However, structural neuroimaging studies in early stages of the illness are limited by small sample sizes yielding inconsistent findings. The purpose of this systematic review and meta‐analysis, therefore, was to identify regional grey matter volume (GMV) changes that are consistently associated with first episode of mania (FEM). Methods: Following PRISMA guidelines, we conducted a systematic search of the literature to identify Voxel‐Based Morphometry (VBM) studies in FEM patients compared with healthy individuals. We then conducted a voxel‐wise meta‐analysis using Seed‐based d‐Mapping technique. Finally, we performed univariate meta‐regression analyses to explore the potential effects of moderator variables including age, gender, and percentage of lithium users on GMV alterations. Results: We identified 15 VBM studies and included 12 studies in the meta‐analysis. Four studies found no regional differences in GM volumes while other 11 studies reported volume changes in frontal and temporal regions as well as anterior cingulate cortex (ACC), cerebellum and basal ganglia. The meta‐analysis revealed a single cluster of GMV reduction in bilateral pregenual ACC in patients with FEM compared to healthy individuals ( P < .001). The Egger's test showed no evidence of publication bias at peak voxel level ( P = .447). Meta‐regression analyses revealed no significant effects of moderators evaluated. Conclusions: Structural brain changes are evident in the early stages of bipolar disorder. GMV reduction in bilateral pregenual ACC is the most consistent finding in VBM studies of FEM.